Comparação da rigidez entre parafusos transarticulares e fitas de alta resistência para as lesões ligamentares tarsometatarsais em um modelo cadavérico - Tiago Soares Baumfeld (2023)
Introduction: ligament injuries of the tarsometatarsal joint complex (TMT) range from high-energy injuries with significant midfoot instability to low-energy injuries with subtle subluxations or instability without gross dislocation. Recently, treatment options that allow a more physiological fixation of this multiplanar joint are being evaluated. The aim of this study was to compare the stability of the TMT joint in a cadaveric model after a classic repair with transarticular screws and fixation with high-resistant tapes. Methods: 24 paired frozen cadaver leg and foot specimens (12 individuals under 65 years of age) underwent two different types of TMT joint complex injuries: partial and complete. Two different fixation methods were compared: transarticular screws and high-resistant tapes (FiberTape®). The specimens were fixed on a rotation platform to stress the joints by applying 400 N of axial load and internal and external rotation. Six distances between intact, injured and repaired states were measured and compared using a 3D digitizing arm in order to assess the stability of the TMT joint complex. Analysis of variance and panel data in smoothed distribution graphs were used for the grouped analysis of the 864 measurements obtained. P<0.05 was used to consider statistical significance. Results: using distribution graphs and analyzing the pooled data, it was observed that there was no difference between the two stabilization methods, but the tapes had less variability and the observed distance reductions were closer to the mean. The variability of stabilization with screws was 2.9 times greater than with tape (p<0.001). Conclusion: fixation with high-resistance tapes presented stability similar to transarticular fixation with screws in ligament injuries of the TMT joint complex and exhibited less variability.